META ANALYSIS THE EFFECT OF INTEGRATED SCIENCE TEACHING MATERIALS WITH LITERACY ON STUDENT LEARNING OUTCOMES - Engla Pratama Putri Krismonika; Asrizal Asrizal (Universe, 2021)
Science learning in the 2013 curriculum is carried out on an integrated basis to improve student learning outcomes. However, based on previous research, the real conditions in schools show that the integration of science material and students' literacy skills is still low. The solution to overcome this problem is to use teaching materials that contain literacy. The purpose of this study was to determine the effect size of integrated science teaching materials with literacy on student learning outcomes in terms of class level, themes, types of teaching materials, literacy and learning outcomes. This study uses a meta-analysis method that examines 13 articles. Journal criteria used are national journals consisting of 11 articles and international journals consisting of 2 articles. Based on the results of the study, it can be understood that:1) integrated science teaching materials are more effectively used in class VIII with an effect size of 1.70 is very high category.2) integrated science teaching materials are more effective for use on the theme of motion, waves of respiratory health and digestive health.3) integrated science teaching materials are more effectively used with an effect size of 1.95 is very high category.4) integrated science teaching materials are more effectively used in the digital era literacy with an effect size of 2.21 very high category.5) integrated science teaching materials are effective for increasing student learning outcomes.